Illicit drug trafficking via postal services: A scoping review of economic-criminological context and estimation methods - Agnese Raimondi; Julien Chopin; Stefano Caneppele; Toni Männistö; Ari-Pekka Hameri; Juha Hintsa (Journal of Economic Criminology)
Efficient and interconnected logistics networks, like postal services, provide powerful tools for criminal groups to organize cross-border drug trafficking by exploiting legitimate infrastructure. Despite postal services becoming inadvertent facilitators in smuggling, focused research on this logistical channel is scarce and scattered due to its multidisciplinary, cross-country nature. This paper conducts a systematic scoping review to explore three primary questions: (1) how drug trafficking through postal services is conceptualized, (2) the estimated volume of these illicit flows, and (3) the methodologies employed to determine these estimates. Our scoping review, which covers studies from 2006 to 2024, identified 49 relevant articles. The findings indicate that the inherent characteristics of the postal system limit its detection capacity, thereby increasing its appeal for smuggling activities. With criminals thus increasingly shifting to online operations and postal remote shipments, cross-border enforcement agencies need to enhance their awareness of the cross-border illicit trade dimension and their responsiveness to the phenomenon, as well as deepen their digital readiness and ensure digital-based coordinated intelligence. This study emphasizes that the fragmentation of knowledge, combined with the multitude of players involved in monitoring and enforcement activities, demands tight transnational cooperation to ensure enforcement effectiveness and prevent digital asymmetries.